ANALISIS DETERMINAN CADANGAN DEVISA ASEAN-5 - Liza Febrina. (2022)
This research was conducted to determine the effect of interest rate, net export, and inflation rate on foreign exchange reserves. This research uses five countries with the highest foreign exchange reserves in ASEAN including Indonesia, Malaysia, Singapore, Thailand, and Phillippines. Determination of the sample using a saturated sampling technique with five countries during 2009-2019, so the total sample is 55 data. The data used is secondary data obtained from World Bank. Hypothesis testing in this study used Panel Data Analysis with the Eviews 10 program and a significance level of 5% (0.05). The results partially show that the interest rate and the net export have an effect on foreign exchange reserves, while inflation rate has no effect on foreign exchange reserves. The results also show that simultaneously the three independent variables have an effect on foreign exchange reserves.